2019
DOI: 10.1097/wad.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors Characteristic of Autism Spectrum Disorder in a Geriatric Cohort With Mild Cognitive Impairment or Early Dementia

Abstract: Introduction-Autism spectrum disorder (ASD) represents a heterogeneous cluster of clinical phenotypes that are classically diagnosed by the time of adolescence. The possibility of late-life emergence of ASD has been poorly explored.Methods-In order to more fully characterize the possibility of late-life emergence of behaviors characteristic of ASD in MCI and AD, we surveyed caregivers of 142 older persons with cognitive impairment from the University of Kentucky Alzheimer's Disease Center Longitudinal Cohort u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…It was indicated that more than 10 percent of people diagnosed with autism from age 40 to 60 develop a dementia condition such as AD within 15 years [ 71 ]. Moreover, recent research data in a geriatric cohort with mild cognitive impairment or early dementia demonstrate that ASD behaviours may appear de novo of degenerative dementia and autistic behaviours are more prevalent in those with early-onset dementia [ 72 ]. The same research group indicated a correlation of autism-like behaviours with increased levels of Tau and neurofibrillary pathology in the frontal lobes at autopsy in subjects with late-life dementia [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that more than 10 percent of people diagnosed with autism from age 40 to 60 develop a dementia condition such as AD within 15 years [ 71 ]. Moreover, recent research data in a geriatric cohort with mild cognitive impairment or early dementia demonstrate that ASD behaviours may appear de novo of degenerative dementia and autistic behaviours are more prevalent in those with early-onset dementia [ 72 ]. The same research group indicated a correlation of autism-like behaviours with increased levels of Tau and neurofibrillary pathology in the frontal lobes at autopsy in subjects with late-life dementia [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now widely recognized that there is substantial overlap between the two conditions, based on genetic underpinnings, epidemiological similarities, and the high rates of cooccurrence (Wood, 2017). Interestingly, behavioral characteristics of ASD have been described in individuals with MCI or early dementia, demonstrating the possibility of late-life emergence of behaviors characteristic of ASD as part of MCI or AD (Rhodus et al, 2019) (Table 1). Moreover, the genetic basis of ASD and AD implies common associations like memory deficits, cognition changes, demyelination, oxidative stress and inflammation, a fundamental part of both disorders (Table 1) (Khan et al, 2016).…”
Section: Similarities Between Asd and Other Neuropsychiatric Disorders Including Bpsdmentioning
confidence: 99%
“…During pregnancy, both environmental and genetic risk factors may affect inflammatory response of new-borns, hence altering postnatal brain development (Adams-Chapman and Stoll, 2006). These genetic and environmental factors can directly elicit chronic neuroinflammation which in turn may (Rhodus et al, 2019) Similarities of ASD and BPSD (Rhodus et al, 2019) Common mechanisms of ASD and AD (Khan et al, 2016) -Deficits in social communication and social interaction -Restricted, repetitive patterns of behavior, interests, or activities including repetitive movements, use of objects, or speech -Inflexibility in terms of routines modulate neuronal function and immune response via glia activation, or directly by affecting neuronal function (Depino, 2013) (Figure 2). Valproic acid (VPA), as an environmental risk factor, elicited activation in different brain regions, with evidence of long-lasting glia activation in the hippocampus and the cerebellum (Lucchina and Depino, 2014).…”
Section: Neuroinflammation In Asd and Comparison With Other Neurocognitive Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Del total de los participantes el mayor porcentaje correspondía a sujetos con diagnóstico de EA, ante lo cual los autores concluyeron que el cuadro clínico de TEA se hace evidente en sujetos que cursan con EA a medida que este proceso neurodegenerativo aumenta su severidad en términos de deterioro cognitivo. 91 Estas asociaciones con EA no resultan extrañas, ya que, este tipo de demencia manifiesta no sólo compromiso cognitivo, si no que también sintomatología conductual la cual se porta en sujetos con TEA. 92 En concordancia, diversos autores postulan la existencia de un posible TEA subclínico a lo largo de la vida, el cual se manifiesta sólo cuando el funcionamiento cognitivo se ve comprometido debido a lesiones neurológicas o eventos neurodegenerativos en edad avanzada.…”
Section: Demencias Y Teaunclassified